2012
DOI: 10.4172/2155-952x.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine versus Bupivacaine in Postoperative Pain Control

Abstract: Objective: The aim of this study was to compare between 2 types of long acting anesthetics: bupivacaine 0.5% and ropivacaine 0.75%, in terms of their duration of anesthesia, duration of analgesia and their effect in controlling postoperative pain after surgical removal of impacted lower third molars. Material and Methods:This study was conducted on fifty subjects referred to the Oral Surgery Department, Faculty of Dentistry, Mansoura University, for surgical removal of impacted lower third molar. Subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…9,10 The potency of ropivacaine versus bupivacaine has been found out to be in a ratio of 3:2 according to previous studies. 9,11 Mansour et al, 12 found bupivacaine 0.5% and ropivacaine 0.75% to be equipotent in their study. Similar concentration of the drugs were used by Goldstein et al, 13 Porika et al 14 Both the groups were comparable with respect to demographic characteristics like age, gender, weight and ASA class.…”
Section: Discussionmentioning
confidence: 76%
“…9,10 The potency of ropivacaine versus bupivacaine has been found out to be in a ratio of 3:2 according to previous studies. 9,11 Mansour et al, 12 found bupivacaine 0.5% and ropivacaine 0.75% to be equipotent in their study. Similar concentration of the drugs were used by Goldstein et al, 13 Porika et al 14 Both the groups were comparable with respect to demographic characteristics like age, gender, weight and ASA class.…”
Section: Discussionmentioning
confidence: 76%
“…However, one important limitation of nerve blocks, in general, is the short duration of action of the local anesthetic. Even with agents with a longer duration of action, like bupivacaine and ropivacaine, the duration of analgesia is often inadequately sustained in the postoperative period[ 29 ]. Prolonging the duration of analgesia by increasing the dose of local anesthetic entails the risk of adverse events involving the cardiovascular and central nervous systems[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This would be related to the voltage dependent sodium channels. Unlike ropivacaine, bupivacaine exhibits more pronounced neurological toxicity, but with equivalent efficacy to bupivacaine [58] [59] [60] [61] [62]. Thus, because of this pronounced cardiovascular effect, we preferred bupivacaine to ropivacaine.…”
Section: Local Anestheticmentioning
confidence: 99%